PSYCHOLOGICAL FACTORS OF TEACHERS' PROFESSIONAL DEVELOPMENT - Rakhmanova Nigina Aminjonovna (Web of Journals Publishing, 2025)
This article is about the psychological factors of the professional development of teachers, and studies the main factors influencing the professional growth of a teacher and the development of his psychological state. The professional activity of teachers is carried out in complex, constantly changing and changing conditions. Therefore, the psychological preparation of teachers, their role in their professional development is important. This article studies the psychological foundations of the professional development of teachers, their motivation, struggle against professional stress, striving for self-development, and social relations with students.
Keywords: Professional development of educators, psychological factors, motivation, stress, self-development, social relationships.